Konversi Energi Surya Menjadi Sistem Pendingin Menggunakan Photovoltaic dan Pendingin Termoelektrik yang Dipasang Paralel - Muhammad Isya Ramdhany; Rifky (Prosiding Seminar Nasional Teknoka, 2023)
The results of converting solar energy into electrical energy by a photovoltaic system can be utilized for a cooling system. This cooling system is a combination of a photovoltaic system and a thermoelectric cooling system. The electrical energy generated by the photovoltaic system is converted by the thermoelectric cooler into a temperature difference on both of its sides. On the hot side of the thermoelectric cooler, heat is expelled as much as possible so that the cold side can absorb as much heat as possible. The objective of this research is to obtain the cooling performance coefficient and the lowest possible temperature in the cooling space. The research method employed is experimental. Before conducting testing and data collection, a research device is first constructed. The research device used in this study consists of a frame for the solar panel and another frame for the cooler. Solar cells are placed on the upper part of the solar panel frame, while the cooler frame contains a cooling space with walls lined with styrofoam, aluminum, styrofoam, and plywood (from the inside out). This study uses three modules of TEC-12706 thermoelectric type, each equipped with three fans. Data collected include sunlight intensity, wind speed, environmental temperature, air humidity, temperature on the cold side and hot side of the thermoelectric cooler, current and voltage entering the thermoelectric module, and the temperature inside the cooling space. The research results indicate that the coefficient of performance (CoP) for the cooling space is 1.33, and the lowest temperature achieved in the cooling space is 22.2°C.